O2 mass transfer in an oscillatory flow reactor provided with smooth periodic constrictions. Individual characterization of kL and a - A. Ferreira (2015)
In the present work the superficial gas velocities (uG) and the oscillatory conditions (frequency andamplitude) effects on the gas-liquid mass transfer process in a novel oscillatory flow reactor providedwith smooth periodic constrictions (OFR-SPC) are experimentally evaluated. The liquid-side mass transfer coefficient, kL, and the specific interfacial area, a, are studied individually. The specific interfacial areais obtained using the new automatic image analysis technique developed by Ferreira et al. (2012). Theexperimental results of volumetric liquid side mass transfer coefficient (kLa), Sauter mean diameter(d32) and gas holdup (eG), and the calculated values of a and kL, are correlated with the superficial gasvelocity and the power density (P=V), in order to be used in scale-up processes and in comparisons withthe literature. The results show that kLa increases with both superficial gas velocity and oscillatory conditions, the last ones having the highest impact on the mass transfer process. The increase in the oscillation motion (frequency and amplitude) results in bubble size reduction (from 7 mm, withoutoscillation, to 1 mm, with oscillation), in bubble average residence time increase and, consequently,in a increase. A kL increase with d32 decrease is observed, showing the importance of hydrodynamic phenomena on kL, specially, when very low bubbles sizes are presented in oscillatory flow reactors.